Alexander Bombom on the role BecA-ILRI Hub played in his research and development journey - Bombom, A. (International Livestock Research Institute, 2020)
Alexander Bombom is a forage crop breeder at the National Livestock Resources Research Institute (NaLIRRI), which is part of the bigger National Agricultural Research Organization (NARO) in Uganda. In this video, Alexander details his journey towards realizing impact among farmers in Uganda and the role that the Biosciences eastern and central Africa (BecA)-ILRI Hub played in it.